Obesity and other health determinants across Europe: The EURALIM Project. Issue 6 (1st June 2000) - Beer-Borst, S; Morabia, A; Hercberg, S; Vitek, O; Bernstein, M S; Galan, P; Galasso, R; Giampaoli, S; Houterman, S; McCrum, E; Panico, S; Pannozzo, F; et al.
Abstract : STUDY OBJECTIVE: EURALIM (EURope ALIMentation), a European collaborative study, aimed to determine and describe the extent to which European data on risk factor distributions from different populations could be pooled and harmonised in a common database for international comparisons. SETTING: Seven independent population-based surveys from six European countries (France, Italy, Northern Ireland/United Kingdom, Spain, Switzerland, the Netherlands). METHODS: Data for 18 381 women and 12 908 men aged 40–59 were pooled in a common database. Central statistical analyses on major cardiovascular risk factors were conducted with careful consideration of methodological issues, including differences in study designs, data assessment tools, and analytic techniques used. MAIN RESULTS: Because of the detected variability among methods used, direct comparisons of risk factor distributions and prevalences between studies were problematic. None the less, comparisons of within population contrasts by sex, age group, and other health determinants were considered to be meaningful and apt, as illustrated here for obesity. Results were targeted and disseminated to both the general public and public health professionals and framed in the context of a European information campaign. CONCLUSIONS: International and national comparisons between existing locally run studies are feasible and useful, but harmonisation methods need improvement. Development of an international risk factor surveillance programme based on decentralised data collection is warranted. In the meantime, risk factor contrasts across populations can be used as a basis for targeting needed public health intervention programmes.